Flow structure within a vegetation patch in a gravel-bed river - Jahadi Mahsa; Afzalimehr Hossein; Rowinski Paweł M. (Journal of Hydrology and Hydromechanics, 2019)
Investigation of the interactions between submerged vegetation patch and flow structure is of crucial importance for river engineering. Most of hydraulic models have been presented for fully developed flows over uniform vegetation in the laboratory conditions; however, the mentioned interactions are complex in river flows where the flow is not developed along small patch. This reveals a gap between developed and non-developed flow along the vegetation patch. This study was conducted in a gravel-bed river in the central Iran. The results reveal that the flow structure in evolving flow (non-developed flow) along the patch resembles that in shallow mixing layer. Accordingly, a shallow mixing layer model and modified equations are combined to quantify evolving area along the patch. The evolving shallow mixing layer equations for the flow along a non-uniform vegetation patch reach a reasonable agreement with field data. However, the spreading coefficient of this model less than one was reported in literature, 0.06 and 0.12. In addition, the flow immediately downstream the vegetation patch behaves similar to a jet and is parameterized by two conventional models, conventional logarithmic law and mixing layer theory. These models present a reasonable agreement with the measured velocity profiles immediately downstream the patch.